Data regarding the computational fluid dynamics simulations of an airfoil with plasma actuator in unsteady flow - Maria Grazia De Giorgi; Valentina Motta; Antonio Suma (Data in Brief, 2020)
The data regard the analysis reported in the research article “Influence of actuation parameters of multi-DBD plasma actuators on the static and dynamic behavior of an airfoil in unsteady flow” [1]. The data are related to the study focused on the evaluation of the effects of an active flow control system on the performance of an airfoil in an unsteady flow, with particular focus on the influence of actuation parameters on the global performances. Keywords: Load alleviation, Plasma actuation, Active flow control, Oscillating airfoils, Actuation law, Stability control